Release of volatile compounds from polymeric microcapsules mediated by photocatalytic nanoparticles - Marques, Juliana Filipa Gouveia (2013)
In this study we propose a suitable method for the solar-activated controlled release of volatile compounds from polymeric microcapsules bonded with photocatalytic nanoparticles. These reservoirs can find applications, for example, in the controlled release of insecticides, repellents, or fragrances, amongst other substances. The surfaces of the microcapsules have been functionalized with TiO2 nanoparticles.Upon ultraviolet irradiation, redox mechanisms are initiated on the semiconductor surface resulting in the dissociation of the polymer chains of the capsule wall and, finally, volatilization of the encapsulated compounds. The quantification of the output release has been performed by gas chromatography analysis coupled with mass spectroscopy.